A novel inertial impact piezoelectric actuator with adjustable angle vibrators - Lin, Shengrong; Ma, Jijie; Li, Jianping; Li, Shengjie; Wang, Minghao; Hu, Yili; Wen, Jianming (International journal of mechanical sciences, 2023)
•A novel inertial piezoelectric actuator utilizing adjustable angle vibrators is proposed.•The established static theoretical model reveals that the actuator has four motion states.•The motion states and output performances can be optimized by adjusting driving voltage and inclination angle. Inertial piezoelectric actuators based on the impact principle have attracted much attention in precision positioning applications recently. However, the control strategy that can utilize the synergistic effect of driving force and friction force to optimize the motion states and output performances of this type of actuator is an important method yet to be studied. In this work, a novel inertial impact piezoelectric actuator with a pair of adjustable angle vibrators is proposed. The static analysis results obtained from the established static theoretical model indicate that the actuator has four motion states, namely stationary state, forward state without backward motion, forward state with backward motion, and unstable state, which are determined by the coupling relationship between the driving voltage and the inclination angle. The underlying operation mechanism revealed by the static analysis is then verified by the dynamic analysis and experimental results. Besides, the effects of the inclination angle of vibrators on the output performances of the actuator such as resolution, velocity, repeatability, and so on, are also obtained in experiments. Experimental results indicate that the resolution of the actuator is 0.24 μm under a driving voltage of 10 V with a 60° inclination angle. Under the condition of 90 V and 75°, the maximum velocity reaches 15.54 μm/s. The control strategy successfully optimizes the motion state and two output performances of the inertial impact piezoelectric actuator by conveniently adjusting its inclination angle for meeting various demands in different applications. [Display omitted]